Interest in dietary pattern, social capital, and psychological distress: a cross-sectional study in a rural Japanese community - Motohashi, Kazuyo (BioMed Central, 2013)
BACKGROUND: Among life-style factors affecting mental health, dietary habits are becoming a public health concern in their relation to psychological distress and social capital. We examined associations between interest in dietary pattern, social capital, and psychological distress with a population-based cross-sectional study in rural Japan. METHODS: A total of 16,996 residents of a rural town in northern Japan aged 30–79 years participated in this questionnaire survey. The questionnaire gathered data about socio-demographic variables, psychological distress, issues related to dietary habits, including interest in dietary pattern, and the social capital factors of reciprocity and sense of community belonging. Factors related to psychological distress were analyzed by using multiple logistic regression analysis. RESULTS: A high interest in dietary pattern was significantly associated with a high level of social capital. In addition, an association between interest in dietary pattern and frequencies of intake of vegetables and fruits was confirmed. The multiple logistic regression analyses showed significant associations between interest in dietary pattern, social capital, frequency of intake of vegetables, and psychological distress after adjusting for socio-demographic variables. Low interest in dietary pattern was positively associated with psychological distress after adjusting for socio-demographic variables (OR = 2.18; 95%CI: 1.69-2.81). Low levels of both reciprocity and sense of community belonging were associated with psychological distress after adjusting for socio-demographic variables (OR = 3.46 with 95%CI of 2.10–5.71 for reciprocity, and OR = 7.42 with 95%CI of 4.64–11.87 for sense of community belonging). CONCLUSION: Low interest in dietary pattern, low frequency of intake of vegetables, and low levels of social capital were significantly associated with psychological distress after adjusting for socio-demographic variables.